1975
DOI: 10.1002/cne.901630402
|View full text |Cite
|
Sign up to set email alerts
|

The pattern of projection of cortical areas 17, 18, and 19 onto the laminae of the dorsal lateral geniculate nucleus in the cat

Abstract: The projection of cortical areas 17, 18, and 19 onto the laminar part of the dorsal lateral geniculate nucleus was investigated with degeneration methods and with the autoradiographic axon tracing method. In agreement with previous accounts, degenerating cortical axons stained by the Nauta method were restricted to laminae A, A1, C and to the interlaminar zones. In contrast, adjacent sections stained with the Fink-Heimer method showed fine dust like degeneration throughout all of the laminae of the nucleus. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(63 citation statements)
references
References 42 publications
7
56
0
Order By: Relevance
“…There is evidence that projections both to and from area 18 are unevenly distributed through the depth of the A layers (Updyke, 1975;Geisert, 1985;Erisir et al, 1998); therefore, for both the areas 17 and 18 axon populations, each A layer was subdivided into top, middle, and bottom thirds. To ensure that the mediolateral distribution of boutons could be assessed accurately, the layers were also divided into 90-mwide columns oriented perpendicular to the laminar borders.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…There is evidence that projections both to and from area 18 are unevenly distributed through the depth of the A layers (Updyke, 1975;Geisert, 1985;Erisir et al, 1998); therefore, for both the areas 17 and 18 axon populations, each A layer was subdivided into top, middle, and bottom thirds. To ensure that the mediolateral distribution of boutons could be assessed accurately, the layers were also divided into 90-mwide columns oriented perpendicular to the laminar borders.…”
Section: Methodsmentioning
confidence: 99%
“…In the cat, it involves at least three separate cortical areas, 17, 18, and 19 (Kawamura et al, 1974;Updyke, 1975), each of which forms a characteristic pattern of corticof ugal connections. In particular, although bulk labeling experiments have shown that the area 17 and 18 pathways both terminate in all of the layers and compartments of the dLGN complex, there is evidence to suggest subtle differences in their bouton distributions (Updyke, 1975) and choice of postsynaptic targets (Vidnyánszky and Hámori, 1994).…”
Section: Abstract: Lateral Geniculate Nucleus; Visual Cortex; Corticmentioning
confidence: 99%
See 2 more Smart Citations
“…It seems dear from these results that feedback plays a role in spatially loca.li"'ed processing. Evidence to support this comes from the precise topography of the feedback projections (Updyke, 1975). This means that a simple role as the sourec of arousal cannot be conjectured for the feedback projections.…”
Section: Corticogeniculate Feedbackmentioning
confidence: 99%